Body weight gain after radioiodine therapy of hyperthyroidism - Scheidhauer, K.; Odatzidu, L.; Kiencke, P.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2002)
Aim: Analysis and follow up of body weight after radioiodine therapy (RITh) of hyperthyroidism, since excessive weight gain is a common complaint among these patients. Methods: Therapy and body weight related data of 100 consecutive RITh-patients were retrospectively analysed from the time before up to three years after RITh. All patients suffered from hyperthyroidism (Graves‘ disease or autonomy), but were adjusted to euthyroid levels after RITh. Patients‘ data were compared to a control group of 48 euthyroid patients out of the same ambulance and during the same time scale. Results: All patients (RITh and controls) gained weight over the time. There was no statistically significant difference in BMI development over three years between RITh-patients and controls (5.5% resp. 4.9% increase). In the first year after RITh, weight gain of the RITh patients was higher indeed, but lower in the follow up, resulting in the same range of weight gain after three years as the controls. Besides that women showed a slightly higher increase of BMI than men, and so did younger patients compared to elder as well as patients with overweight already before RITh. Conclusions: An initially distinct increase of body weight after RITh of hyperthyroidism is mainly a compensation of pretherapeutic weight loss due to hyperthyroidism. Presupposing adequate euthyroid adjustment of thyroid metabolism after therapy, RITh is not responsible for later weight gain and adipositas.
Keywords: Body weight; body mass index; hyperthyroidism; radioiodine therapy